2018
DOI: 10.1590/1678-4324-2017160221
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Cerebrospinal Fluid Promotes Proliferation and Neural Differentiation of Stromal Mesenchymal Stem Cells Derived from Bone Marrow

Abstract: Embryonic cerebrospinal fluid (E-CSF) contains many neurotrophic and growth factors, acts as a growth medium for cortical progenitors, and can modulate proliferation and differentiation of neural stem cells. Mesenchymal stem cells (MSCs) are multipotential stem cells that can differentiate into several types of mesenchymal cells as well as nonmesenchymal cells, such as neural cells. In the present study, the effect of E-CSF on proliferation and neural differentiation of bone marrow mesenchymal stem cells (BM-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Different effect of CSF on stem cells has been also observed depending on their origin. Shokohi et al (2017) observed that CSF affected the expression of marker MAP2 (increase) in murine BM-MSCs, but did not affect MSCs derived from dental pulp (Haratizadeh et al, 2017). In addition, rat CSF increased the expression of the neural marker Nestin in dental pulp MSCs (Haratizadeh et al, 2017) and rat BM-MSCs (Mafikandi et al, 2019).…”
Section: Effect Of Csf On Other Cell Typesmentioning
confidence: 90%
See 2 more Smart Citations
“…Different effect of CSF on stem cells has been also observed depending on their origin. Shokohi et al (2017) observed that CSF affected the expression of marker MAP2 (increase) in murine BM-MSCs, but did not affect MSCs derived from dental pulp (Haratizadeh et al, 2017). In addition, rat CSF increased the expression of the neural marker Nestin in dental pulp MSCs (Haratizadeh et al, 2017) and rat BM-MSCs (Mafikandi et al, 2019).…”
Section: Effect Of Csf On Other Cell Typesmentioning
confidence: 90%
“…Culturing bone marrow mesenchymal stem/stromal cells (BM-MSCs) in CSF resulted in morphological changes to present astrocyte dendrite and axon-like cells [human CSF and human BM-MSCs; (Ye et al, 2011;Ge et al, 2015)] neurite length [rat CSF and murine BM-MSCs; (Shokohi et al, 2017)]; long spindle-shaped cells [rat CSF and rat BM-MSCs; (Mafikandi et al, 2019)]; mature neurons and dendrite-like cells presenting Nissl bodies [rabbit CSF and rabbit BM-MSCs; (Otify et al, 2014)]. Moreover, CSF from newborn rats of healthy mothers (N-CSF, normal-CSF) has been shown to undergo more rapid morphological change into long spindle-shaped cells than CSF from newborn rats of mothers with hypothyroidism (HTH-CSF, hypothyroidism-cerebrospinal fluid) (Mafikandi et al, 2019).…”
Section: Effect Of Csf On Other Cell Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell suspension was then centrifuged at 15000 rpm for 5 min, and subsequently cultured in 25 cm 2 flasks. The adhered cells from the third passage were used to be treated with CSF (Shokohi et al, 2017).…”
Section: Isolation and Expansion Of Bm-mscsmentioning
confidence: 99%
“…To determine the most effective concentration of CSF, cells cultured in DMEM, 3% FBS and 1% pen/ strep were exposed to different concentrations of CSF [i.e., 5 ,7 and 10 /100 (v/v)] for a week. One concentration was selected as yielding the optimum CSF concentration (Shokohi et al, 2017).…”
Section: Treatment Of Bm-mscs Using Csfmentioning
confidence: 99%